PCcGE: Personalized Chinese Couplet Generation and Evaluation Framework Based on Large Language Models - Zhigeng Pan; Xianliang Xia; Fuchang Liu; Minglang Zheng (Applied Sciences)
Couplets, consisting of a pair of clauses, are an important form of Chinese intangible cultural heritage, playing a significant role in the education and transmission of traditional Chinese culture. By engaging in couplet creation, students can enhance their Chinese comprehension and expression skills, literary creativity, and cultural identity. Personalized Chinese couplet (PCc) generation entails creating paired clauses that meet specific requirements while adhering to certain linguistic rules (e.g., morphological and syntactical symmetry). However, generating PCcs and evaluating the results is a challenging task that requires both cultural context and language understanding. Large Language Models (LLMs) have powerful learning and language comprehension abilities, providing new possibilities for addressing the challenges. In this study, we propose a framework for generating and evaluating PCcs using LLMs. First, we construct a couplet database, then use a retrieval method and design a specific prompt to provide a pair of clauses as references to guide the LLM following the rules of couplet style. Second, we construct a custom PCc generation dataset to train the base model, improving its ability for this task. Finally, we introduce a debate method based on LLMs to evaluate the quality of the generated couplets. By simulating adversarial human debate processes, it obtains more comprehensive and nuanced reference data for evaluation purposes. The experimental results show that our approach effectively generates and evaluates couplets. Reduced creation difficulty promotes couplet education and the preservation of Chinese intangible cultural heritage. Positive feedback from participants indicates that our framework can enhance user engagement, offer a positive PCc creation experience, and contribute to the education and transmission of couplet culture.